Global Journalism between Dream and Reality: A comparative study of The Times, Le Monde and De Standaard. (17th August 2016) - Van Leuven, Sarah; Berglez, Peter
Abstract : Global journalism is a practice that differs from traditional foreign correspondence. Instead of only covering distant events, it actively interconnects the local with the global. However, while some researchers claim that its practice has been incorporated into everyday news production as a natural response to the increasing interconnectedness of our globalized society, others see few empirical signs of its presence, and instead consider it to be a utopian vision for less "national provincialism" among the world's media. These contrasting views on the evidence for global journalism in the news call for more empirical research. The purpose of this study is thus to examine the prevalence of global journalism in mainstream news media. The article provides, first, an operationalization of global journalism and, second, a quantification of its presence or absence in the news output of three national newspapers, The Times, Le Monde and De Standaard, by means of a quantitative content analysis covering the period January to June 2013 (N = 850). According to our main results, a quarter of all articles include at least one building block of global journalism, and a fifth of all articles are centered on a global event and/or present a global outlook on the reported matter. Le Monde is the most "global" newspaper, as it exhibits the most examples of global journalism. However, the other two newspapers to a greater extent embed global outlooks in their domestic news sections, which might be viewed as an emerging way of producing globalized news discourse in a social reality with ever-more blurred distinctions between domestic and global reality.